Global gains from trade liberalization - Haichao Fan; Edwin L.-C. Lai; Han Steffan Qi (Center for Economic Studies and ifo Institute (CESifo), 2012)
What has been the overall global welfare impact of the accession to the World Trade Organization of a large country like China, or the global welfare impact of the completion of the Uruguay round of GATT negotiations? Can we come up with a simple user-friendly formula to calculate the global welfare impact of the simultaneous trade liberalization of a number of countries? How sensitive is the answer to the assumption of the trade model? We find a striking answer to these questions. We find that, for a very broad class of models and settings, the global welfare impact of trade liberalization in a country, or a simultaneous liberalization of a number of countries, is given by the same simple formula. We find that the global welfare impact of the simultaneous trade liberalization of different countries only depends on two sets of statistics: (i) the ratio of the value of bilateral trade between each and every pair of trading partners and global income; and (ii) the change in exporting cost for each and every pair of trading partners. Most interestingly, the formula applies to a very broad class of models and settings, which include the general Ricardian model (including, for example, Anderson, 1979, and Eaton and Kortum, 2002), the models of Krugman (1980), Melitz (2003) and its extensions, and the extensions of these models to the multi-sectoral case, multi-factor production technology, multi-stage production, the existence of tradable intermediate goods and the existence of a large outside good sector in each country. We find that global welfare would have been 0.05% lower in the year 2008 if China had not gained accession to the WTO in 2001.
Keywords: F10; F12; F13; 330; global welfare; trade liberalization; trade cost